PENGARUH INTEGRASI TEKNOLOGI DAN ROLE MODEL DOSEN TERHADAP GROWTH MINDSET MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN UNIVERSITAS NEGERI SURABAYA - Rossi Ardiansyah, Ananda; Ibadil Maula, Farij (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital era, marked by the digital native phenomenon, has created a paradox in higher education. On one hand, technology offers abundant access to information; on the other, it fosters instant thinking patterns and the dominance of a fixed mindset among students. This condition calls for systematic efforts to cultivate a growth mindset through an integrated approach. This study aims to examine and analyze the effect of technology integration and lecturer role models on students' growth mindset, both partially and simultaneously. The theoretical framework is grounded in the Technology Acceptance Model (TAM) by Davis (1989), Social Learning Theory by Bandura (1977), and Growth Mindset Theory by Dweck (2006). A quantitative approach was employed using a purposive sampling technique. The population consisted of 188 students of the Office Administration Education Study Program at Universitas Negeri Surabaya, class of 2022, with a sample of 134 respondents determined through the Slovin formula. Data were collected through a five-point Likert scale questionnaire distributed via Google Form and analyzed using IBM SPSS Statistics 25. The findings reveal that technology integration has a positive and significant effect on growth mindset (sig. 0.000; t = 4.995), as does the lecturer role model (sig. 0.001; t = 3.452). Simultaneously, both variables significantly influence growth mindset (sig. 0.000; F = 47.520), with a coefficient of determination of 42%. This study concludes that directed technology integration combined with inspiring lecturer role models synergistically fosters a conducive learning ecosystem for students' growth mindset.